Активність NAD+-залежних ензимів мітохондрій нирок у щурів за умов різної забезпеченості раціону нутрієнтами - Voloshchuk, Oksana; Boichuk, Andriana (ЧНУ, 2022)
The aim of this work was to evaluate the activity NAD+-dependent dehydrogenases of Krebs cycle in kidney of rats under the conditions of different sucrose and protein content in a diet. The activity of isocitrate dehydrogenase was evaluated based on the amount of accumulated NADН during conversion of isocitrate to α-ketoglutarate. The activity of malate dehydrogenase was determined from NADH accumulation in reaction of malate oxidation, at λ = 340 nm. The activity of α-ketoglutarate dehydrogenase was measured by intensity of α-ketoglutarate oxidation, spectrophotometrically at λ = 417 nm. The animals were divided into the following experimental groups: I – control group (C); II – animals receiving low-protein ration (LP); III – animals receiving high-sucrose diet (HS); IV – animals receiving lowprotein high-sucrose diet (LP/HS). It has been shown, that by rats group kept on a low-protein diet isocitrate dehydrogenase activity was increased, without any significantly compared changes in α-ketoglutarate dehydrogenase and malate dehydrogenase activities. A similar tendence is typical for animals maintained on a low-protein/high-sucrose diet. At the same time isocitrate dehydrogenase, α-ketoglutarate dehydrogenase and malate dehydrogenase activities exceeded control values in group of animals feeded by high-sucrose diet the most. From results we got, it can be concluded, that activation of NAD+-dependent dehydrogenases of Krebs cycle in mitochondrial kidney fraction of rats received a high-sucrose diet can be considered as one of possible links in mechanism of kidney injury progression. Our finding allows to substantiate the approaches for kidney complications treatment biochemically under nutrient imbalance.
ACTIVITY OF KIDNEY MITOCHONDRIAL NAD+ -DEPENDENT DEHYDROGENASES IN RATS UNDER CONDITIONS OF DIFFERENT NUTRIENT SUPPLY
Keywords: nutrients, kidney, mitochondria, isocitrate dehydrogenase, α-ketoglutarate dehydrogenase, malate dehydrogenase